Elegiske sensibiliteter. Følelsens æstetik set fra en genre. - Lønneker, Ane Martine Kjær (Passage - Tidsskrift for litteratur og kritik, 2016)
Ane Martine Kjær Lønneker: “Elegiac Sensibilities. The Aesthetics of Feeling from the Point of View of Genre” The article discusses the concept of mode and examines the historical circumscription of the elegiac mode. This is done with special regard to the 18th century critical writings on distinctive feelings connected to the elegy. The article argues that the components that make up a mode in the case of the elegiac are associated with an affective repertoire. The 18th century idea of mode as Empfindungsweise (Schiller) can thus be regarded as an incitement to study how genres frame emotional tonalities and how aesthetic feelings are cultivated by historical genre discourses.